Foundations in the Ottoman Empire and its Contributions to the Social Life - Emre Rıfat Güpgüpoğlu (Resolusi: Jurnal Sosial Politik, 2018)
From the past to the present day, societies have established institutions to address their needs for social assistance, solidarity and security within their structures. Some social assistance and social security practices established in modern societies had been carried out by the foundation in Islamic societies in the past. In the Ottoman Empire, as in the Turkish-Islamic states, the foundation institution had played an essential role in the provision of the social order and the cooperation and solidarity of the society. The allocation of private property to the public service gives a social content to the property in question. The allocation of the wealth and income of the founders of the foundation to public service and transferring them to the persons belonging to the lower income group reveal the social function of the foundation. In this context, the main aim of the study is to reveal the function of the foundation institution in the context of social assistance, social solidarity and social security in the Ottoman Empire after first considering the definition, function and a short history of the foundation.